Dampak Pengawasan Pemerintah Terhadap Pencegahan Korupsi Pada Kasus Walikota Cimahi - Fathin, Muhammad Qais; Safitri, Annida; Nurpadilah, Fitri Hasanah; Renova, Deta; Darmawan, Ivan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The prevention of corruption, especially in local government in Cimahi, is highly dependent on government supervision. Three mayors of Cimahi have been implicated in various corruption cases, indicating the need to improve the supervisory system. The study of corruption cases in Cimahi, their origins, and supervision efforts made by government agencies. Based on qualitative and literature study, using data from various relevant literatures to support the analysis. The study shows that corruption in Cimahi is influenced by a systemic culture of corruption in the government and the absence of systemic change due to the irregularities of the case. The Cimahi City Government has taken steps to prevent corruption, including anti-corruption socialization, bureaucratic reform, and increased transparency through the Monitoring Center for Prevention. It is hoped that the Cimahi government can become a transparent government, structuring good governance and free of corruption as well as a city government that is more confident in its citizens.